Ensuring safe drinking water: microbial evaluation of restaurants in Patuakhali district, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2024)
Drinking water (DW) from restaurants is a major source of microbial exposure among consumers that causes diseases. The evaluation of the microbiological quality of the drinking water in restaurants provides the foundation for appropriate action to minimize contamination and protect patrons from food-borne illnesses. The aim of this study was to determine the microbial quality of restaurant’s drinking water. A total of 20 water samples were collected in sterile test tube from the restaurants in Dumki and Patuakhali Sadar Upazilla of Patuakhali district. Total viable count on Nutrient agar and total coliform count on MacConkey agar were done by standard plate count (SPC) technique and bacterial identification by different biochemical tests. The present study found all the water samples (100%) were contaminated with bacteria in the ranges of 4.50 × 104 to 7.00 x 105, and 95% of the samples were contaminated with E. coli, and the range was 0 to 2.8 × 102. A total of 26 distinct bacterial colony were isolated from various samples and morphologically characterized. Based on biochemical characteristics, we identified a total of 10 bacterial species. Among them, 6 (23.10%) were both for Enterobacter aerogenes and Staphylococcus epidermidis followed by Escherichia coli (E. coli) 5 (19.23%), Pseudomonas spp. 3(11.54%), and rest of the Vibrio cholera, Klebsiella oxytoca, S. auerous, Bacillus spp., Aeromonas salmonicida and Salmonella spp. were 1 (3.85%) for each.  A diverse range of fecal coliform, enteropathogenic and pathogenic bacteria present in samples indicates the unsanitary handling and storage practices in restaurants; this could make customers more susceptible to illnesses and ailments linked to water.Asian Australas. J. Food Saf. Secur. 2024, 8(1), 5-12